2016
DOI: 10.1088/1361-6501/28/1/015904
|View full text |Cite
|
Sign up to set email alerts
|

Analytical electron microscope based on scanning transmission electron microscope with wavelength dispersive x-ray spectroscopy to realize highly sensitive elemental imaging especially for light elements

Abstract: An analytical electron microscope based on the scanning transmission electron microscope with wavelength dispersive x-ray spectroscopy (STEM-WDX) to realize highly sensitive elemental imaging especially for light elements has been developed. In this study, a large-solid-angle multi-capillary x-rays lens with a focal length of 5 mm, long-time data acquisition (e.g. longer than 26 h), and a drift-free system made it possible to visualize boron-dopant images in a Si substrate at a detection limit of 0.2 atomic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…B elements are the light elements with low-energy, and they are not easily detected because their low-energy characteristic X-rays are easily absorbed by the baseline. 32 And EDX mapping display uniform distribution of C and O elements, and O elements with higher brightness. In addition, considering the impact of carbon grids in the sample preparation process of TEM, actually, the content of C is lower for IPA@HBA than that we observed in their EDX mapping.…”
Section: Water Stimulus-responsive Rta Propertiesmentioning
confidence: 99%
“…B elements are the light elements with low-energy, and they are not easily detected because their low-energy characteristic X-rays are easily absorbed by the baseline. 32 And EDX mapping display uniform distribution of C and O elements, and O elements with higher brightness. In addition, considering the impact of carbon grids in the sample preparation process of TEM, actually, the content of C is lower for IPA@HBA than that we observed in their EDX mapping.…”
Section: Water Stimulus-responsive Rta Propertiesmentioning
confidence: 99%
“…Further, electron cameras 836,837 are often supplemented by secondary signal detectors. For example, elemental composition is often mapped by EDX spectroscopy, electron energy loss spectroscopy 838,839 (EELS) or wavelength dispersive spectroscopy 840,841 (WDS). Similarly, electron backscatter diffraction [842][843][844] (EBSD) can detect strain 845,846…”
Section: Microscopesmentioning
confidence: 99%
“…We evaluated the minimum mass fraction (MMF) to validate the system improvement [12,13]. In this paper, we define MMF by equation (2.6) and figure 5.…”
Section: Minimum Mass Fraction (Mmf)mentioning
confidence: 99%
“…For B detection, the minimum mass fraction (MMF) [11,12] has been reported to be several at. % under a 1 nA beam current with an acquisition time of a few minutes [13]. Recently, in the AEM based on STEM-WDX, Koguchi et al reported that they could visualize B dopant images in a Si substrate at a detection limit of 0.2 at.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation